The Fourth International Conference on Dense Z-Pinches 1997
DOI: 10.1063/1.53929
|View full text |Cite
|
Sign up to set email alerts
|

Application of 2-D simulations to hollow Z-pinch implosions

Abstract: Los Alamos National Laboratory, an affirmative actiodequal opportunity employer, is operated by the University of California for the US. Department of Energy under contract W-7405-ENG-36. By acceptance of this article, the publisher recognizes that the U.S. Government retains a nonexclusive, royalty-free license to publish or reproduce the published form of this contribution, or to allow others to do so, for U.S. Government purposes. Los Alamos National Laboratory requests that the publisher identify this arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 2 publications
2
4
0
Order By: Relevance
“…Iineouts of the images in the r-z plane show that the wavelength of the RT structure is in the range of 1 to 3 mm, in agreement with RMHC simulations [15,24,40] and the Heuristic Model.…”
Section: A Measurementssupporting
confidence: 61%
See 2 more Smart Citations
“…Iineouts of the images in the r-z plane show that the wavelength of the RT structure is in the range of 1 to 3 mm, in agreement with RMHC simulations [15,24,40] and the Heuristic Model.…”
Section: A Measurementssupporting
confidence: 61%
“…The data show that the narrow (<5 ns) radiation pulses generated by intecwire gaps below -0.5 mm can be realistically simulated by the 2-D Eulerian radiationmagnetohydrodynamic code (E-RMHC) [23,24], in which Rayleigh-Taylor (RT) growth dominates the implosion dynamics in the r-z plane. For these simulations, the array is idealized as a uniform, cylindrically-symmetric shell with a random-density variation in the r-z plane that seeds the RT instability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peterson and co-workers [13][14][15][16] have successfully shown agreement in radiation quantities and physical appearance using a random density seed for loads on four different experimental machines, Pegasus, 13 Procyon, 14 Saturn, 15 and Z. 16 Roderick and co-workers, 7,13 Hammer et al, 17 and Douglas et al 18 have also successfully modeled Saturn experiments using a random density seed. These calculations showed that the MRT instability alone describes the majority of the pinch dynamics and that only a single variable Í‘the initial perturbation amplitudeÍ’ is necessary to accurately model the experimental data without resorting to modified or "anomalous" physical parameters.…”
Section: Development Of Random Seedsmentioning
confidence: 86%
“…At the same time, MRT instability's effects on the Z-pinch stagnation and radiation were studied numerically, which has been found to provide good matches with experiments. Peterson [47,[51][52][53] has successfully shown agreement in radiation quantities and physical appearance using a random density seed for loads on four different experimental machines, Pegasus [47], Procyon [51], Saturn [52], and Z [53]. Hammer [54], and Douglas [55] have also successfully modeled Saturn experiments using a random density seed.…”
Section: The Mrt Instabilitymentioning
confidence: 89%